1973
DOI: 10.21236/ada035979
|View full text |Cite
|
Sign up to set email alerts
|

Compaction Characteristics of Earth-Rock Mixtures. Report 1. Vicksburg Silty Clay and Degray Dam Clayey Sandy Gravel

Abstract: I ie. las a9If ierl ictinty ClNSS11tii tion DOCUMENT CONTROL DATA.-R & D '5ecur,ayc ef latcato. .1 1,a),, boad, Of 4 1ry; and 0-in e ian ,,ust!In a be ar ~r, hen th. everett report). tioa.11"ad, IOft)GINA TiNG ACTtVIYY (Cor~prte auhor) Is, 04CvPORT Secrpry 1iLASII A t.ON U'. S. Army Enigincer Warterways Exprirment Station l~nclauoitied Vicksburg, Mississippi a 1. GROUP 3 RaEPORT tTLIE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, a consensus has not been reached yet to choose a compactness parameter to be controlled for the scalped or scalped/replaced specimen in comparison with that of the original soil, while this parameter is determinant of the obtained shear strength. Different parameters have been actually considered: (i) the absolute dry unit weight γ d (Reiffsteck et al 2007), (ii) the relative dry unit weight γ d /γ d,max (Leslie 1963, Donaghe & Torrey III 1985, (iii) the relative density D R (Al-Hussaini 1983, Dano 2001 or (iv) the dry unit weight γ retained d of the retained fraction in the original soil (El Dine 2007). The scalping procedure has been extensively studied by several authors who showed divergent conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a consensus has not been reached yet to choose a compactness parameter to be controlled for the scalped or scalped/replaced specimen in comparison with that of the original soil, while this parameter is determinant of the obtained shear strength. Different parameters have been actually considered: (i) the absolute dry unit weight γ d (Reiffsteck et al 2007), (ii) the relative dry unit weight γ d /γ d,max (Leslie 1963, Donaghe & Torrey III 1985, (iii) the relative density D R (Al-Hussaini 1983, Dano 2001 or (iv) the dry unit weight γ retained d of the retained fraction in the original soil (El Dine 2007). The scalping procedure has been extensively studied by several authors who showed divergent conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…The scalping procedure has been extensively studied by several authors who showed divergent conclusions. It has been shown that the scalping procedure can lead to an underestimation (Al-Hussaini 1983, Donaghe & Torrey III 1985, Reiffsteck et al 2007, El Dine 2007, an overestimation (Dano 2001, Dorador & Villalobos 2020 or a good estimation (Leslie 1963) of the shear strength of coarse-grained soils. A few studies on the scalping/replacement procedure have been carried out; and, like the 4 scalping one, the conclusions about this procedure are contradictory (Donaghe & Torrey III 1985, Reiffsteck et al 2007, Hamidi et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sieve scalped/replaced data obtained by Donaghe and Townsend (1975) can be used to illustrate the potential errors introduced by using the maximum dry density of the minus site from that seen in Figure 38 for maximum dry density. The predicted values for maximum dry density were relatively satisfactory up to about 35 percent gravel, whereas the predictions for optimum water content were best above that gravel content.…”
mentioning
confidence: 99%
“…It would not be a significant exercise to predict maximum dry densities of the total materials using the data of Donaghe and Townsend (1975) or USBR (1963) because only one set of gradations were used in those studies.…”
mentioning
confidence: 99%